PENINGKATAN KEMAMPUAN BELAJAR HITUNG PADA ANAK MELALUI RAGAM PERMAINAN KREATIF - Araujo, Domingos De; Kusumastuti, Berta; Widyaningrum, Susanna Nur; Sidharta, Anastasia Putranti; Hardiyanti, Bernadeta Tri (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
The numeric skills of the children in RW 08, Jogoyudan, Kali Code, Yogyakarta and their parentâs motivation to accompany their children to study were far from our hope. These problems encouraged us to conduct a program entitled âPeningkatan Kemampuan Belajar Hitung pada Anak melalui Ragam Permainan Kreatifâ. This program was aimed to increase the childrenâs numeric skills and to help their parents to motiavte their children to study. The method was learning through creative games, which consisted of traditional games and games created by us. The result showed that the childrenâs numeric skills and the support of their parents increased.